Method for preparing green low-carbon concrete material from solid wastes
By crushing and modifying the waste blue bricks, they are used as recycled fine aggregate in concrete, the problem of strength reduction caused by the admixture of blue brick particles in concrete is solved, and high-strength and green environmental protection effects are achieved.
Patent Information
- Application Number
- CN202411298425.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-03-28
AI Technical Summary
A large amount of blue brick particles in concrete will lead to a significant decrease in strength, limiting the reuse ratio of waste blue bricks.
By crushing the discarded blue bricks into recycled fine aggregates and modifying them in a modified solution made of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate, and ethanol, the connecting force of the recycled fine aggregates in cement slurry is enhanced.
On the premise that all modified recycled fine aggregates replace river sand, the strength of concrete remains high, and waste blue bricks can be widely used in concrete production, reducing the limitation of reuse and achieving a green and environmentally friendly effect.
Abstract
Description
Technical Field
[0001] The invention relates to the field of building materials, and in particular to a method for preparing green low-carbon concrete materials by utilizing solid waste. Background Art
[0002] Solid waste refers to solid waste materials generated by humans in various activities. Solid waste mainly includes three categories: industrial waste, agricultural waste and domestic waste. With the development of industry, the amount of industrial waste is increasing. Fully recycling industrial waste can greatly reduce environmental pollution.
[0003] With the development of the construction industry and the implementation of a large number of old house renovation projects, a large number of discarded blue bricks have been generated. In order to reuse the discarded blue bricks, some artists use the discarded blue bricks for carving, but the consumption rate of discarded blue bricks by artistic creation is limited.
[0004] Concrete is one of the main building materials. Concrete contains a large amount of aggregates. Using waste green bricks in concrete to replace natural aggregates is one of the important ways to quickly consume waste green bricks. However, it is found in actual application that if a large amount of green brick particles are added, the strength of the concrete will be significantly reduced, resulting in green brick particles only being able to replace river sand in small amounts. The application of waste green bricks is still greatly restricted. Therefore, there is still room for improvement. Summary of the invention
[0005] In order to increase the strength of concrete while adding a large amount of green brick particles, the present application provides a method for preparing green low-carbon concrete materials using solid waste.
[0006] The present application provides a method for preparing green low-carbon concrete materials using solid waste, which adopts the following technical scheme: A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into particles of 3-5 mm to obtain recycled fine aggregate; Step 2), mixing the recycled fine aggregate with the modifying liquid, and drying after the modification is completed to obtain modified recycled fine aggregate; Step 3), 315-317 parts of cement, 35-36 parts of fly ash, 410-420 parts of modified recycled fine aggregate, 770-780 parts of coarse aggregate, and 5.8-6.2 parts of admixture are mixed to obtain a premix; Step 4), adding 100 parts of water to the premix, mixing evenly, to obtain a concrete mixture; Step 5), injecting the concrete mixture into a mold, curing, and demoulding, thereby utilizing solid waste to prepare green low-carbon concrete materials; In the step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate and ethanol.
[0007] By adopting the above technical scheme, the recycled fine aggregate is modified in a modifying liquid prepared by mixing isopropyl titanate, allyl glycidyl ether, octadecyl phosphate and ethanol, so that the modified recycled fine aggregate is not easy to rob water in the cement slurry, and the cement slurry can enter the pores of the modified recycled fine aggregate in the form of slurry, thereby greatly improving the connection between the cement stone and the modified recycled fine aggregate, thereby making the strength of the cured concrete higher. Under the premise that the modified recycled fine aggregate completely replaces the river sand, the strength of the concrete can still be maintained at a high level, and it is not easy to affect the performance of the concrete, so that the waste blue bricks can be widely used in the concrete production, reducing the restrictions on the reuse of waste blue bricks, and achieving the effect of green environmental protection.
[0008] Preferably, the mass ratio of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate and ethanol is 6-8:9-11:7-9:220-280.
[0009] By adopting the above technical scheme and specifically selecting the mass ratio of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate and ethanol, the modification effect on the recycled fine aggregate is better, and the obtained concrete has higher strength and better quality.
[0010] Preferably, in step 2), the mass ratio of the recycled fine aggregate to the modified liquid is 1:1.8-2.2.
[0011] By adopting the above technical solution and specifically selecting the mass ratio of recycled fine aggregate to modifying liquid, a better modification effect can be ensured, while reducing the consumption of modifying liquid, thereby having a higher economic value.
[0012] Preferably, in the step 2), the recycled fine aggregate is mixed with the modified liquid, heated to 60-70° C., and stirred at a constant temperature for 90-120 min.
[0013] By adopting the above technical solution, by heating to 60-70°C and stirring at a constant temperature for 90-120 minutes, the modification effect is better, the strength of the concrete can be better improved, and the performance of the concrete is better.
[0014] Preferably, in step 3), the admixture is a compound of a water reducing agent and an early strength agent.
[0015] By adopting the above technical solution and adding water reducing agent and early strength agent, the construction performance can be improved and the difficulty of concrete construction can be reduced.
[0016] Preferably, the mass ratio of the water reducing agent to the early strength agent is 3.6-3.8:2.2-2.4.
[0017] By adopting the above technical solution and specifically selecting the mass ratio of the water reducing agent and the early strength agent, the water reducing effect and the early strength effect are both better, and the concrete quality is better.
[0018] Preferably, the water reducer is a polycarboxylate water reducer.
[0019] By adopting the above technical solution and specifically selecting the polycarboxylate water-reducing agent, the water-reducing effect is better, the dosage is less, and the negative impact on the concrete performance is reduced.
[0020] Preferably, the early strength agent is calcium formate.
[0021] By adopting the above technical solution and specifically selecting calcium formate, the early strength effect is better and the concrete performance is better.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application modifies the recycled fine aggregate in a modifying liquid prepared by mixing isopropyl titanate, allyl glycidyl ether, octadecyl phosphate and ethanol, the modified recycled fine aggregate is not easy to snatch water in the cement slurry, and the cement slurry can enter the pores of the modified recycled fine aggregate in the form of slurry, thereby greatly improving the connection between the cement stone and the modified recycled fine aggregate, thereby making the strength of the cured concrete higher. Under the premise that the modified recycled fine aggregate completely replaces the river sand, the strength of the concrete can still be maintained at a high level, and the concrete performance is not easily affected, so that the waste blue bricks can be widely used in concrete production, reducing the restrictions on the reuse of waste blue bricks, and achieving a good green environmental protection effect.
[0023] 2. In the present application, it is preferred to specifically select the mass ratio of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate and ethanol to achieve a better modification effect on the recycled fine aggregate, and the obtained concrete has higher strength and better quality.
[0024] 3. In the present application, it is preferred to heat to 60-70°C and stir at a constant temperature for 90-120 minutes to achieve a better modification effect, better improve the strength of the concrete, and better the performance of the concrete. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments.
[0026] Example 1 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate.
[0027] Step 2), 500 kg of recycled fine aggregate and 900 kg of modified liquid are put into a stirring tank, heated and kept at a constant temperature of 60°C, a rotation speed of 120 r / min, stirred for 90 minutes, the solid is filtered out, and dried at 110°C for 60 minutes. After drying, modified recycled fine aggregate is obtained.
[0028] Step 3), 315kg cement, 35kg fly ash, 410kg modified recycled fine aggregate, 770kg coarse aggregate, 3.6kg water reducer, 2.2kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0029] Step 4), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain concrete mixture.
[0030] Step 5), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0031] In step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol, and the mass ratio of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol is 6:9:7:220.
[0032] Isopropyl titanate is commercially available, CAS number: 546-68-9.
[0033] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0034] Octadecanyl phosphate is commercially available, CAS number: 4724-47-4.
[0035] The ethanol is industrial-grade anhydrous ethanol with a concentration of 95%, which is commercially available and has a CAS number of 64-17-5.
[0036] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0037] The fly ash is sourced from commercially available, first-grade fly ash.
[0038] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0039] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0040] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0041] The discarded blue bricks are from the market.
[0042] Example 2 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate.
[0043] Step 2), 500 kg of recycled fine aggregate and 1000 kg of modified liquid are put into a stirring tank, heated and kept at a constant temperature of 65°C, a rotation speed of 120 r / min, stirred for 105 min, the solid is filtered out, and dried at 110°C for 60 min. After drying, modified recycled fine aggregate is obtained.
[0044] Step 3), 316kg cement, 35.5kg fly ash, 415kg modified recycled fine aggregate, 775kg coarse aggregate, 3.7kg water reducer, 2.3kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0045] Step 4), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain concrete mixture.
[0046] Step 5), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0047] In step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol, and the mass ratio of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol is 7:10:8:250.
[0048] Isopropyl titanate is commercially available, CAS number: 546-68-9.
[0049] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0050] Octadecanyl phosphate is commercially available, CAS number: 4724-47-4.
[0051] The ethanol is industrial-grade anhydrous ethanol with a concentration of 95%, which is commercially available and has a CAS number of 64-17-5.
[0052] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0053] The fly ash is sourced from commercially available, first-grade fly ash.
[0054] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0055] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0056] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0057] The discarded blue bricks are from the market.
[0058] Example 3 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate.
[0059] Step 2), 500 kg of recycled fine aggregate and 1100 kg of modified liquid are put into a stirring tank, heated and kept at a constant temperature of 70°C, a rotation speed of 120 r / min, stirred for 120 min, the solid is filtered out, and dried at 110°C for 60 min. After drying, modified recycled fine aggregate is obtained.
[0060] Step 3), 317kg cement, 36kg fly ash, 420kg modified recycled fine aggregate, 780kg coarse aggregate, 3.8kg water reducer, 2.4kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0061] Step 4), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain concrete mixture.
[0062] Step 5), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0063] In step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol, and the mass ratio of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol is 8:11:9:280.
[0064] Isopropyl titanate is commercially available, CAS number: 546-68-9.
[0065] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0066] Octadecanyl phosphate is commercially available, CAS number: 4724-47-4.
[0067] The ethanol is industrial-grade anhydrous ethanol with a concentration of 95%, which is commercially available and has a CAS number of 64-17-5.
[0068] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0069] The fly ash is sourced from commercially available, first-grade fly ash.
[0070] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0071] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0072] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0073] The discarded blue bricks are from the market.
[0074] Example 4 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate.
[0075] Step 2), 500 kg of recycled fine aggregate and 1000 kg of modified liquid are put into a stirring tank, at room temperature, at a rotation speed of 120 r / min, stirred for 105 min, the solid is filtered out, and dried at 110° C. for 60 min. After drying, modified recycled fine aggregate is obtained.
[0076] Step 3), 316kg cement, 35.5kg fly ash, 415kg modified recycled fine aggregate, 775kg coarse aggregate, 3.7kg water reducer, 2.3kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0077] Step 4), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain concrete mixture.
[0078] Step 5), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0079] In step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol, and the mass ratio of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol is 7:10:8:250.
[0080] Isopropyl titanate is commercially available, CAS number: 546-68-9.
[0081] Allyl glycidyl ether is commercially available, CAS number: 106-92-3.
[0082] Octadecanyl phosphate is commercially available, CAS number: 4724-47-4.
[0083] The ethanol is industrial-grade anhydrous ethanol with a concentration of 95%, which is commercially available and has a CAS number of 64-17-5.
[0084] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0085] The fly ash is sourced from commercially available, first-grade fly ash.
[0086] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0087] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0088] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0089] The discarded blue bricks are from the market.
[0090] Comparative Example 1 A method for preparing green low-carbon concrete material using solid waste, compared with Example 2, the only difference is: In the modified solution of step 2), an equal amount of silane coupling agent KH-570 is used to replace isopropyl titanate.
[0091] Silane coupling agent KH-570 is commercially available, CAS number: 2530-85-0.
[0092] Comparative Example 2 A method for preparing green low-carbon concrete material using solid waste, compared with Example 2, the only difference is: In the modified solution of step 2), an equal amount of silane coupling agent ZQ-172 is used to replace allyl glycidyl ether.
[0093] Silane coupling agent ZQ-172 is commercially available, CAS number: 1067-53-4.
[0094] Comparative Example 3 A method for preparing green low-carbon concrete material using solid waste, compared with Example 2, the only difference is: In the modified solution of step 2), an equal amount of silane coupling agent KH-602 is used to replace n-octadecyl phosphate.
[0095] Silane coupling agent KH-602 is commercially available, CAS number: 3069-29-2.
[0096] Comparative Example 4 A method for preparing green low-carbon concrete material using solid waste, compared with Example 2, the only difference is: In the modified solution of step 2), an equal amount of silane coupling agent KH-570 is used to replace isopropyl titanate; an equal amount of silane coupling agent ZQ-172 is used to replace allyl glycidyl ether; and an equal amount of silane coupling agent KH-602 is used to replace octadecyl phosphate.
[0097] Silane coupling agent KH-570 is commercially available, CAS number: 2530-85-0.
[0098] Silane coupling agent ZQ-172 is commercially available, CAS number: 1067-53-4.
[0099] Silane coupling agent KH-602 is commercially available, CAS number: 3069-29-2.
[0100] Comparative Example 5 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate.
[0101] Step 2), 316kg cement, 35.5kg fly ash, 415kg recycled fine aggregate, 775kg coarse aggregate, 3.7kg water reducer, 2.3kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0102] Step 3), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0103] Step 4), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0104] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0105] The fly ash is sourced from commercially available, first-grade fly ash.
[0106] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0107] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0108] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0109] The discarded blue bricks are from the market.
[0110] Comparative Example 6 A method for preparing green low-carbon concrete material using solid waste comprises the following steps: Step 1), 316kg cement, 35.5kg fly ash, 415kg fine aggregate, 775kg coarse aggregate, 3.7kg water reducer, 2.3kg early strength agent are put into a stirring tank, the speed is 60r / min, stirring for 10min, mixing evenly, and obtaining a premix.
[0111] Step 2), add 100 kg of water to the premix, rotate at 60 r / min, stir for 5 min, mix evenly, and obtain a concrete mixture.
[0112] Step 3), injecting the concrete mixture into the mold, sprinkling water for curing for 3 days, demolding, sprinkling water for curing for the 7th day, and standing and curing for the 28th day, thereby preparing green low-carbon concrete materials using solid waste.
[0113] The cement is ordinary Portland cement, Runfeng cement, factory specification: P.O42.5R.
[0114] The fly ash is sourced from commercially available, first-grade fly ash.
[0115] The coarse aggregate is basalt crushed stone, which is commercially available and has a particle size of 18-22 mm.
[0116] The water reducer is polycarboxylic acid water reducer, which was purchased from Jinan Quanchi New Materials Co., Ltd.
[0117] The early strength agent is calcium formate, which is commercially available, CAS number: 544-17-2.
[0118] The discarded blue bricks are from the market.
[0119] Fine aggregate is natural river sand, which is commercially available and has a particle size of 3-5 mm.
[0120] Experiment 1 According to GB / T50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete", the 7-day compressive strength and 28-day compressive strength of the test samples made of the concrete mixtures prepared in each embodiment and comparative example were tested.
[0121] The specific test data of Experiment 1 are shown in Table 1.
[0122] Table 1 7-day compressive strength (MPa) 28-day compressive strength (MPa) Example 1 45.7 60.5 Example 2 46.1 60.9 Example 3 46.3 61.3 Example 4 44.9 59.4 Comparative Example 1 41.4 54.7 Comparative Example 2 42.1 55.8 Comparative Example 3 41.8 55.3 Comparative Example 4 41.1 54.4 Comparative Example 5 38.4 50.8 Comparative Example 6 45.5 60.2 According to the data comparison of each embodiment and comparative example in Table 1, it can be obtained that the compressive strength of each embodiment is similar to that of comparative example 6, among which embodiments 1-3 are even slightly higher than comparative example 6. It can be seen that the modified recycled fine aggregate obtained by modifying the blue brick particles with a modifier prepared by compounding isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol completely replaces the natural river sand, is not likely to cause the strength of the concrete to decrease, can reach the strength level of natural aggregate, and the quality of the obtained concrete is better.
[0123] The strength of Example 4 is slightly lower than that of Comparative Example 6. It can be seen that carrying out the modification at 60-70°C can improve the modification effect and further enhance the strength of the concrete.
[0124] The strength of Comparative Example 5 is significantly lower than that of Comparative Example 6. In Comparative Example 5, the blue brick particles are not modified. It can be seen that directly using unmodified blue brick particles to completely replace natural river sand will lead to a significant decrease in the strength of concrete.
[0125] The strength of Comparative Examples 1-4 is higher than that of Comparative Example 5 but significantly lower than that of each embodiment and Comparative Example 6. It can be seen that when conventional modifiers are used to replace isopropyl titanate, allyl glycidyl ether, and octadecyl phosphate alone or in full, and the modified recycled fine aggregate modified from green brick particles completely replaces natural river sand, although the concrete strength is improved to a certain extent compared with the direct use of unmodified green brick particles, there is still a large gap compared with the concrete strength using pure natural river sand. It can be seen that after using conventional modifiers to destroy the composite system of isopropyl titanate, allyl glycidyl ether, octadecyl phosphate, and ethanol, the modification effect decreases, and the strength of the obtained concrete decreases significantly, and it is difficult to reach the level of natural aggregates.
[0126] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing green low-carbon concrete materials using solid waste, characterized in that: The following steps are involved: Step 1), crushing the waste green bricks into 3-5 mm particles to obtain recycled fine aggregate; Step 2), mixing the recycled fine aggregate with the modification liquid, and drying after the modification is completed to obtain the modified recycled fine aggregate; Step 3), 315-317 parts of cement, 35-36 parts of fly ash, 410-420 parts of modified recycled fine aggregate, 770-780 parts of coarse aggregate, and 5.8-6.2 parts of admixture are mixed to obtain a premix; Step 4), add 100 parts of water to the premix, mix evenly, and obtain a concrete mixture; Step 5), injecting the concrete mixture into the mold, curing and demoulding, and preparing green low-carbon concrete materials using solid waste; In the step 2), the modified liquid is a compound of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate and ethanol.
2. The method for preparing green low-carbon concrete material using solid waste according to claim 1, characterized in that: The mass ratio of isopropyl titanate, allyl glycidyl ether, n-octadecyl phosphate and ethanol is 6-8:9-11:7-9:220-280.
3. The method for preparing green low-carbon concrete material using solid waste according to claim 2, characterized in that: In the step 2), the mass ratio of the recycled fine aggregate to the modified liquid is 1:1.8-2.
2.
4. The method for preparing green low-carbon concrete material using solid waste according to claim 3, characterized in that: In the step 2), the recycled fine aggregate is mixed with the modified liquid, heated to 60-70° C., and stirred at a constant temperature for 90-120 minutes.
5. The method for preparing green low-carbon concrete material using solid waste according to claim 1, characterized in that: In the step 3), the admixture is a compound of a water reducing agent and an early strength agent.
6. The method for preparing green low-carbon concrete material using solid waste according to claim 5, characterized in that: The mass ratio of the water reducing agent to the early strength agent is 3.6-3.8:2.2-2.
4.
7. The method for preparing green low-carbon concrete material using solid waste according to claim 6, characterized in that: The water reducer is a polycarboxylate water reducer.
8. The method for preparing green low-carbon concrete material using solid waste according to claim 6, characterized in that: The early strength agent is calcium formate.